Perception of Inclusive Democracy and Federalism in the Magar Community of Chitwan (Voice of History, 2025)
This study discusses attitudes among Chitwan Magar activists and leaders regarding the political participation of their community within an inclusive democracy and federal set-up. As such, this study seeks to find out whether these are concretely realised in the society of Magars, with special focus on political inclusion, representation, and expectations. This is reached through key research to assess the status of inclusive democracy and federalism, in the case of the Magars of Chitwan. This study employs a qualitative research design grounded in interpretive and participatory paradigms, using intensive interviews and literature review to explore the perception of the Magar activities of Chitwan and leaders regarding political inclusion and representation within the framework of inclusive democracy and federalism. The findings are contextualised by reviewing secondary sources, both historical and recent studies, on the Magar community. This study concludes that while the Magar community made major contributions to Nepal’s political movements, including the Maoist insurgency, their aspirations for federalism remain largely unfulfilled. Despite past involvement, Magars continue to face political marginalisation, with minimal representation in governance and decision-making. The current federal structure fails to satisfy respondents, who see no cultural or linguistic autonomy as once envisioned during Nepal’s transformation into a federal republic. The notion of inclusive democracy in Nepal is still nascent and demands significant reforms to ensure equitable political representation for indigenous groups like the Magars. Essential steps include strengthening democratic institutions and promoting participatory governance to enhance inclusivity and achieve the federal vision.